Strategi Penguatan Pendapatan Daerah dan Pengembangan Kemandirian Ekonomi Lokal Melalui Instrumen Ekonomi Islam: Studi Tentang Zakat, Infaq, Sedekah, dan Wakaf - Anton Budiyono; Nida Hopia (PRODUCTIVITY: Journal of Integrated Business, Management, and Accounting Research, 2025)
This study aims to examine how zakat, infaq, sadaqah, and waqf can be used strategically to strengthen regional income and encourage local economic independence. This study uses a descriptive qualitative approach. The research subject of this article is Islamic economic instruments which include zakat, infaq, alms, and waqf, as well as their role in increasing local income and building regional economic independence. The data were analyzed using descriptive qualitative methods. The results of the analysis show that the use of zakat, infaq, alms, and waqf has significant potential to increase regional revenue and alleviate poverty. With good and integrated management in public financial policies, zakat, infaq, alms, and waqf can be a solution for sustainable financial and economic independence that is able to overcome various social problems in society. Increasing literacy, professional management, and the use of digital technology will be the key to success in optimizing the potential of zakat, infaq, alms, and waqf in the future, so that the economic independence of a region can be realized properly and effectively